Moral And Cultural Values Reflected In The Novel Pergi By Tere Liye - Anisa Ramadaniya Syafitri; Juairiah Juairiah; Nada Alifa Rahmi; Normeila Santi; Nor Afifah Safira (PT. Sharia Journal and Education Center, 2026)
Tere Liye is one of Indonesia’s most prolific literary figures, whose works are rich in life values that remain relevant to readers. The novel “Pergi” (2018) is a sequel to “Pulang” (2015), narrating the adventures of the main character Bujang in the world of cross-border shadow economies. Beneath its action and adventure narrative, the novel holds a wealth of moral and cultural values worthy of scholarly examination. This study aims to describe and analyze the moral and cultural values contained in the novel Pergi by Tere Liye. The method employed is descriptive qualitative with a content analysis approach. Data were collected through a read-and-note technique from the novel’stext as the primary source, supported by scientific journals and reference books as secondary sources. The findings reveal that Pergi contains moral values encompassing the relationship between humans and themselves (honesty, courage, responsibility), the relationship between humans and others (loyalty, compassion,coopration), and the relationship between human and God(tawakkul, gratitude) the cultural values identified include Malay-Minangkabau cultural values reflected through Bujang’s family background, the values of mutual cooperation (gotong royong) and togetherness, as weel as a representation of multicultural values mirrored in settings spread across various countries. This study concludes that Pergi is not merely a work of entertainment, but rather a medium for the transmission of rich moral and cultural values to its readers.